Rediscovery of the Ochromonas type species Ochromonas triangulata (Chrysophyceae) from its type locality (Lake Veysove, Donetsk region, Ukraine). Issue 6 (1st November 2017) - Andersen, Robert A.; Graf, Louis; Malakhov, Yuriy; Yoon, Hwan Su
Abstract: Ochromonas triangulata, the type species for a genus with over 125 taxa, was collected for only the second time, again from the type locality. Cell morphology, cell division, palmelloid stage and cyst structure generally agreed with the original description. Molecular phylogenetic analysis based on the 18S rRNA gene revealed 13 clades of Ochromonas -like flagellates as well as the clade represented by our O. triangulata strain and the nearly identical strain RCC-21/AC025. We also conducted a concatenated analysis using the 18S rRNA and the rbc L genes, and we recovered the same 14 clades. One clade, containing strains CCAP 933/27 and CCMP1861, previously named Ochromonas tuberculata, was re-identified as Chrysastrella paradoxa and Chrysastrella breviappendiculata, respectively. One clade included the Poterioochromonas strains but we were unable to convincingly connect species names to the strains because authentic strains were unknown or not examined. Organisms in the clade that included the well-known Ochromonas danica were assigned to Chlorochromonas . The generic name Melkoniania gen. nov . was proposed for one distinct clade of marine flagellates. These changes addressed some of the issues associated with the polyphyletic Ochromonas sensu lato but many problems remained.